Techno-economic benefits deriving from optimal scheduling of a Virtual Power Plant: Pumped hydro combined with wind farms. (May 2021) - Cavazzini, Giovanna; Benato, Alberto; Pavesi, Giorgio; Ardizzon, Guido
Abstract: Wind and solar are renewable sources characterized by a great potential but a variable and unpredictable nature. Characteristics that provoke mismatch between power supply and demand which in turns are the source of network control issues. Problems manageable with the installation of large-scale energy storage like Pumped Hydro Energy Storage (PHES). To this purpose, the paper presents a techno-economic analysis for assessing the benefits deriving from the hybridization of a seawater PHES (sPHES) plant with an in-operation wind farm. Plants work as a Virtual Power Plant (VPP) instead of two separate unit. The hybridization aims to avoid the unbalances of the wind farm, having negative impact on both the grid and the wind farm owner itself. The unbalances cause unpredictable deviations from the predicted production and, hence, power production fluctuations faced by the grid with curtailments and/or calls in operation of fossil-fuelled power plants. A VPP techno-economic optimization on a daily bases is performed using the ASD-PSO algorithm while the optimization aim is the revenue maximization. Results show that a VPP composed by a sPHES and a wind farm and with a single owner, is able to manage the wind farm production, improving the revenue of 6.8% compared to plants acting separately on the market. The VPP approach is also convenient in the case of a joint venture between the plants owners. But, in this case, the revenue is increased only of 0.4% compared to plants working separately. Finally, results also highlight that, in the Italian electricity market, a sPHES plant alone is not able to generate sufficient revenue to guarantee a reasonable payback time while coupling it with a wind farm increases incomes and working days and avoid cost and grid issues in managing the unpredictable wind farm production. Highlights: A Virtual Power Plant which combines a Pumped Hydro and Wind Farms is modelled. A techno-economic optimization is performed. Real pump-turbine machine curves are used to improve optimization effectiveness. Technical and operating constraints of the PHES are considered in the optimization.